Optimization of energy consumption and costs of wood drying with use of different drying techniques - Gorišek, Željko (Zbornik gozdarstva in lesarstva, 2010)
The time and energy required for wood drying and therefore drying costs are among the highest in wood products manufacturing. Analysis of the drying process costs is very complex and needs to evaluate the cost of investments, energy, labour as well as defects of lumber or added value. In the present research work, we upgraded the computer aided engineering (CAE) model of wood drying processes with the economic evaluation of different drying techniques. By analyzing and comparing the costs of different drying processes, the model is able to predict the transition wood moisture content (MCt) at which the alteration from one to another drying technique would get the best results. The model was verified on data from several air- and kiln-drying experiments on 38 mm thick beech wood (Fagus sylvatica L.) boards. Computer simulation predicted advantages of combined dying beech wood with air predrying and continued and finished with kiln drying. The MCt in the winter period was at about 40% MC and decreased to 23% in favourable climate conditions in spring and summer months. The model can be also used for optimising the combination of other drying techniques.
Keywords: bukev; poraba energije; stroški; sušenje lesa